Prescription Pattern and Blood Pressure Control among Patients on Antihypertensive Medications Attending a Tertiary Hospital in Lagos - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Hypertension is a disease of global public health importance affecting an estimated 1 billion people worldwide. Hypertension accounts for about 10.4 million deaths in 2017. Many guidelines are available for the management of hypertension, but despite this, there are wide variations in physicians’ choice of antihypertensive medications for blood pressure (BP) control.Aims:We reviewed the prescription pattern of antihypertensive medication and the level of BP control in patients with hypertension.Settings and Design:This is a cross-sectional study among hypertensive patients attending follow-up clinics of a tertiary hospital.Methodology:Structured questionnaires were used to collect information on the antihypertensive medications and clinical profiles of the study participants. Questionnaires were administered to participants during the attendance of the follow-up clinic to capture information relevant to the study. Information retrieved from patients includes details about their baseline demographic characteristics, clinical history, antihypertensive drug history and blood BP recordings. The study protocol was reviewed and approved by the institutional ethics committee.Statistical Analysis:Data were analysed using Microsoft Excel 2003 and the Statistical Package for the Social Sciences version 22.0 software.Results:A total of 489 hypertensive patients took part in the study. The study found that the rate of BP control was 44.6% among the participants. Calcium channel blockers (CCBs) are the most common antihypertensive medication prescribed in our clinics. There was no significant relationship between how long a patient had been attending the follow-up clinic and the level of BP control in patients who have attended the clinic for a minimum period of 3 months.Conclusion:BP control was less than optimal in more than half of the participants, and the most commonly prescribed antihypertensive medication were CCBs.